An opinion dynamics model based on affinity and social noise - Liu, Jusheng; He, Jianjia; Qiu, Zhiping; He, Shengxue (Frontiers in Physics, 2022)
Most previous works have studied the evolution of opinions based on the Hegselmann-Krause model, the Deffuant Weisbuch model, and the Sznajd model. However, the influence of social influence on opinions is discussed less. Based on the social influence theory and the Hegselmann-Krause model of opinion dynamics, we introduce the affinity and the social noise in the Hegselmann-Krause model of opinion dynamics and propose an affinity and social noise Hegselmann-Krause model(ASNHK). The influence of affinity degree, affinity threshold, social noise, and personnel heterogeneity on opinion evolution is discussed in experimental analysis. Experimental results show that the affinity between people can improve opinion to form a consensus positively, but the affinity threshold has a negative role contrarily. Besides, when the social noise increases, the opinion will form a consensus, when it increases to a certain value, the opinion will get decentralized. Furthermore, personnel heterogeneity has different effects on opinion evolution. Open-minded individuals are more likely to form a unified opinion, while closed-minded individuals have difficulty unifying their opinions. Overall, this research provides a clearer explanation of the group opinion evolution from social influence.